An improved mouth-piece to prevent environmental contamination during radioaerosol inhalation procedures - Braga, FJHN; Souza, J. F.; Trad, C. S.; Santos, A. C.; Netto, T. G.; Elias, J.; Hindie, E.; Iazigi, N. (Lippincott Williams & Wilkins, 1998)
The literature suggests that environmental contamination is common during labeled aerosol inhalation procedures in nuclear medicine. We have tested an adherent mask to prevent environmental contamination in 70 procedures. Two groups of patients were evaluated, Group 1 (60 inhalation cases in which the mask was used) presented no environmental contamination in 95% of the procedures (means of 553 dpm and 596 dpm before and after inhalation, p > 0.05, mean of the differences before/after inhalation 6.95, SD = 21.2 dpm) and the only 3 cases in which contamination did occur concerned bearded men; Group 2 (10 inhalation cases in which the mask was not used) showed large increases of environmental radioactive levels in 70% of the procedures (means of 601 dpm and 2,756 dpm before and after inhalation, p < 0.05, mean of the differences 3,066, SD = 2,98 dpm), We conclude that such a mask is very helpful in avoiding environmental contamination during radioaerosol inhalation procedures.
Keywords: aerosols; inhalation; contamination, environmental; radiation protection